Brief communication: Correlation between elastic modulus and radiographic density in mandibular cortical bone of colobine monkeys. Issue 1 (6th February 2017) - Rapoff, Andrew J.; Scott McGraw, W.; Duque, Ana; Daegling, David J.
Abstract: Objectives: The relationship between radiographic grayscale and elastic modulus was determined using mandibular cortical bone of colobine monkeys. Quantification of this relationship is critical for establishing absolute measures of structural rigidity of skeletal elements. Materials and methods: We determined the Vickers microhardness values in mandibular bone from two species of African colobine monkeys and related these values to elastic modulus through an empirically determined correlation. We also determined radiographic grayscale values from microcomputed tomographic scans of the mandible in the same regions in which microhardness was sampled. We then correlated modulus to grayscale with a power law relationship. Results: We found that elastic modulus scaled with negative allometry with respect to grayscale with an exponent of 0.77. Discussion: Our results suggest a single exponent can effectively capture the relationship of grayscale to elastic modulus and facilitate development of heterogeneous structural models for use in comparative and computational biomechanical studies.